Critical Synthesis Package: Index for Interdisciplinary Collaboration (IIC) - Sheila Crow (Association of American Medical Colleges, 2015)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health science education of the Index for Interdisciplinary Collaboration (IIC), and (2) a copy of the IIC developed by Laura R. Bronstein, LCSWR, ACSW, PhD. The IIC was designed to measure the perception of collaboration between social workers and other professionals working on an interdisciplinary team. The scale contains 42 items and five subscales: Interdependence, Newly Created Professional Activities, Flexibility, Collective Ownership of Goals, and Reflection on Process. The response options are presented along a 5-point Likert scale (1 = strongly agree, 5 = strongly disagree) for each item. Mean subscale scores and a total scale score can be calculated. Lower scores indicate higher levels of collaboration. Twelve items are reverse scored. An adapted version of the scale, the Modified Index for Interdisciplinary Collaboration (MIIC), was subsequently developed to survey a broader group of health care professionals working on hospice teams and has similar psychometric properties as the IIC. As a result of the rewording of the IIC to create the more broadly applicable MIIC, the MIIC is better for assessing interprofessional teamwork between individuals within the healthcare field, across multiple settings. Unfortunately, the IIC is limited to use with social workers and lacks sufficient theoretical and psychometric development. Although a factor analysis provided strong support for the IIC as a measure of the perception of interdisciplinary collaboration, the high degree of internal consistency suggests the measure may be best thought of as a global measure of perceptions of interdisciplinary collaboration among social workers, rather than one possessing subscales for separate dimensions. Further work is needed to confirm correlations between interdisciplinary collaboration and the factors thought to influence it.